The Gender Shift: Disassociating Gendered Behavior from a Predicted Model of Career Disadvantage Among Female Veterinarians - Plackett, Harriet E M (2016)
In 2000, Akerlof & Kranton published a social identity theory that aimed to link gender identity with the economic outcome of individuals working in gendered organizations. Their theory predicts that females working in a gender labelled ‘male’ occupation should incur economic penalties for exhibiting behaviors that are typically gender stereotyped as ‘female’, and should therefore feel ambiguity towards work in a ‘male’ occupation if they follow traditional gender stereotypes. Although they acknowledge that movement of women into a previously male-dominated workforce will have an influence on their predictions, Akerlof & Kranton (2000) do not discuss in any detail how they expect their predicted outcomes to change. The United Kingdom veterinary industry is currently experiencing an unprecedented gender shift towards a female-dominated workforce, with women outnumbering their male counterparts since 2011 (RCVS, 2014). Historically a gender labelled ‘male’ occupation, veterinary medicine is now an example of a profession that has an occupational gender label that does not match the dominant gender of the workforce. This study uses Akerlof & Kranton’s (2000) social identity theory as a framework of analysis for understanding how female veterinarians are experiencing and understanding gender as a potential barrier to their career progression, and the impact that the gender shift towards a female-dominated workforce is having on those working within it. The findings of the study suggest that the dominance of females in the veterinary profession has a larger influence on predicted economic outcomes for female veterinarians than the Akerlof & Kranton (2000) theory predicts. The respondents of this study expressed feeling no disadvantage as a result of gendered behaviors, and instead perceived that career disadvantage for female veterinarians stemmed from the gendered features of the organizations in which they worked.